Quality management model development for transport-logistic processes of enterprises - Khalipova, N. V.; Lesnikova, I. Y.; Shingur, V. A. (Systems and Technologies, 2018)
Formed the two-phase model for the substantiation of effective measures in quality management of transport-logistic processes of the enterprises’. The first phase involves implementation and development of the process approach in the organization. BPMS-system supports business at all stages of the formation and improvement of the process approach, continuous processes improvement mecha- nism allows you to develop a company management model. The use of BPMS system capabilities allows to not only collect and organize statistical information of existing business processes, but also to monitor their strict implementation. The second phase is based on the usage of the process approach and includes sta-tistical quality management of processes by measuring and monitoring of para- meters. It is expected to receive information on the variation of the process, achievement of the state of statistical stability and obtaining estimates of the pro-cess parameters in this state, with subsequent control of the stability of processes. Proposed the algorithm for revealing unstable processes of the enterprise and determination of their stabilization ways based on statistical management of quality indicators and improvement of transport-logistic processes by means of control cards. The algorithm is based on the usage of a mechanism for improving processes that affects the development of the enterprise management model based on the complete Deming cycle (PDCA). The control function represents the necessary attribute of management, which allows to identify problems and adjust the organization accordingly, before these problems turn into a crisis. The control is carried out by means of preliminary analysis of executable processes. For statistical management of logistics enterprise’s supply processes, per-formed simulation using one of the Statistica software package’s main modules – Industrial Statistics and Six Sigma. Simulation using control cards allowed de-tecting a violation of the processes stability beyond the control limits. Result of the calculations: the construction of a medium-sized map, a multidimensional flow of X-bar and R maps identified the causes of instability. The analysis allowed to suggest ways of the logistics enterprise work improvement through the stabili-zation of supply processes.